Efektivitas Model Problem Based Learning dengan Pendekatan Open Ended Terhadap Kemampuan Pemecahan Masalah Fisika Pada Siswa SMA - Chairatul Umamah; herman jufri andi (Universitas PGRI Semarang, 2020)
This study aims to explain how the effectiveness of Problem Based Learning models with an open ended for physics problem solving abilities of high school students on thermodynamics. This type of research is quasi experimental using nonequivalent control group design. There are two classes in this study, namely the control class with the problem based learning model and experimental class using problem based learning model with open ended approach. The test instrument used was a matter of description. Conclusions are drawn based on the results of data processing and analysis using T-test with SPSS 24.0. the results showed that there was a significant influence on the ability to solve physical problems treated by the problem based learning model with open ended approach by sig 0,032 (α=0,05). Analysis of effect size test results is 0,77 in middle category and N-Gain test results is 0,83 with high category. It can be concluded that Problem Based Learning model with open ended approach is an effective used on students' Problem Solving abilities.